A manifestação da responsabilidade enunciativa e da autoria em produções escritas de alunos do 1ºano do Ensino Médio Formativo - Silva, Denise Aparecida Oliveira da (2022)
This dissertation is part of the line of research on Reading, writing and teaching of Portuguese Language, of the Graduate Program in Portuguese Language by the Pontifical Catholic University of São Paulo. Its theme is the enunciative responsibility and authorship in written productions of students entering High School at the Technical School Dr. Ruth Cardoso, educational institution that is part of the network of the State Center of Technological Education Paula Souza. The research is justified by the difficulty that students entering high school usually face in the production of texts, in particular, in the authorial productions, that require the exposure of their point of view and defense of positioning in relation to a given fact or situation. The research questions that guide us in this study are: 1) How does the expression of the point of view contribute to the enunciative responsibility in the texts produced by the students? 2) How does the enunciative responsibility occur in the analyzed texts? 3) What relationships may be established between the enunciative responsibility and the constitution of authorship? To answer these questions, we established as a general objective: to verify how the enunciative responsibility occurs in texts by produced students of the 1st year of Formative High School. The specific objectives are: a) to identify, describe, analyze and interpret linguistic marks that reveal the students' point of view in texts produced by them; b) to examine the relationship between the expressed point of view and the enunciative responsibility in the analyzed texts; c) to reflect on the correlation between the enunciative responsibility and authorship in the texts produced. With regard to the theoretical contribution on enunciative responsibility, we rely on the assumptions of Adam (2011 [2008]), Rabatel (2008, 2009, 2011, 2015, 2016), Nølke (2001, 2009), Nølke, Fløttum and Norén (2004), Guentchéva et al. (1994), Guentchéva (1994, 1996, 2011, 2014), Rodrigues (2017), Rodrigues, Silva Neto and Passeggi (2018), Passeggi et al. (2010) and Rodrigues e Marquesi (2020). As for the point of view, we take as a basis the studies of Rabatel (2004, 2015, 2016, 2017) and François (2015). On authorship, we are based especially on the studies of Adam (2011 [2008]), Foucault (2009), Bakhtin (1997, 2016), Possenti (2001, 2002) and Léniz and Gómez (2021). Methodologically, this dissertation is qualitative, descriptive and interpretive base, and is based on bibliographic and documentary research. The corpus is composed of five texts of the open letter genre, selected from 40 texts produced by students of the 1st year of High School. The results indicate that the students express a point of view and assume the enunciative responsibility articulated to an authorial voice